Investigation of regulation and mechanism of miR-223 on autophagy of CD4 + T lymphocytes in septic mice - Li, Qi; Xiang, Guoan; Peng, Chouchun; Xie, Lixin; Ji, WenJie (Cellular and Molecular Biology, 2020)
T-lymphocyte dysfunction is most important part of immune dysfunction in sepsis, where dynamic change, especially autophagy of CD4+T lymphocytes is found to be related to disease fate. Our study is to i nvestigate the changes of CD4 + T lymphocytes and their autophagy levels in septic miR-223 −/− mouse model injected intraperitoneally with E. coli.120 male C57BL/6J wild-type. Twenty male miR-223 knockout(miR-223-/-) mice were randomly divided into, according to intraperitoneal injection of normal saline (NS) and E. coli solution, normal saline (WT NS) group, sepsis (WT Sep) group, miR-223 −/− NS group and miR-223 −/− Sep group, respectively. The autophagy related protein was monitored with flow cytometry to observe the autophagy of CD4+T lymphocytes. Flow cytometry showed the proportion of CD4 + T lymphocytes in peripheral blood circulation, alveoli, and spleen of mice in the WT Sep group gradually decreased after surgery, the proportion of cells with autophagic activity in this population of cells was significantly higher than that in the WT NS group, and the proportion of CD4 + T lymphocytes with active autophagic activity in miR-223 −/− mice were significantly decreased, but higher than that in the miR-223 −/− NS group and lower than the level of autophagy in CD4 + T cells of wild-type mice. Thus, miR-223 can up-regulate the level of autophagy in CD4 + T lymphocytes of septic mice, suggesting that miR-223 may be used as a potential target for the prevention and treatment of sepsis.